Consumer Satisfaction as a Mediating Variable: The Impact of Service Quality and Consumer Perception on iPhone Purchase Decisions in Depok City - Alloysius Pamruda Dhika Mahendra; Yohanes Ferry Cahaya; Herni Pujiati; Ilham Nawang Armanda (STIE Tri Bhakti, 2026)
This study examines the influence of service quality and consumer perception on iPhone purchase decisions, mediated by consumer satisfaction among 200 consumers in Depok City, Indonesia. Using Smart PLS-SEM analysis, findings reveal that service quality significantly impacts consumer satisfaction (?=0.412, p<0.001) and purchase decisions (?=0.328, p<0.001). Consumer perception demonstrates significant effects on satisfaction (?=0.385, p<0.001) and purchase decisions (?=0.294, p<0.01). Consumer satisfaction partially mediates the relationship between service quality and purchase decisions (?=0.189, p<0.01), and between consumer perception and purchase decisions (?=0.176, p<0.01). The model explains 68.3% variance in purchase decisions, confirming satisfaction's crucial mediating role in premium smartphone purchasing behavior.